Laryngeal Mucosal Changes in Patients in Laryngo-Pharyngeal Reflux before and after Treatment with Proton Pump Inhibitors (Indian Journal of Public Health Research & Development, 2023)
To evaluate pre and post treatment results based on Laryngeal mucosal changes as assessed by direct videolaryngoscopy/stroboscopy using Belafsky scores. In our study we have evaluated laryngeal changes in patientswith dysphonia and RSI 10 before treatment and after 6 months of treatment with Tab. Pantoprazole and Tab.Mosapride. This prospective study was carried out on 50 patients attending the ENT out patient department ofa tertiary care referral centre over a period of 18 months i.e. from Nov 2008 to Apr 2010. The study showed thatprolonged therapy is required to treat laryngopharyngeal reflux (LPR) effectively and 24 h ambulatory dual probe pHmetry and videolaryngoscopy to assess RFS are the most preferred diagnostic tools in LPR. Dr Speech software forvoice analysis can give an objective assessment of voice changes in LPR before and after treatment. The treatmentconsisting of proton pump inhibiter (PPI) and prokinetic drugs proved to be effective in laryngopharyngeal refluxdisease as improvement was seen in all the parameters including reflux findings score. According to results of ourstudy, 24 h ambulatory dual probe pH-metry, Reflux Finding Score (RFS), can be used as indicators of efficacy oftreatment.
Keywords: Laryngopharyngeal reflux (LPR), Prokinetic drugs, Dysphonia